Profitability analysis of motorboat operation plying the route Iloilo City to Jordan, Guimaras. - Gadavan, Charito G.; Jancorda. Cornelio V. (Miag-ao, Iloilo University of the Philippines Visayas, Division of Social Sciences, 2008)
This paper was designed to determine the profitabilty of moterboat operation plying the route between Iloilo City and Jordan, Guimaras. Motorboat operation is a major industry that plays a significant role in the local economy of both Iloilo and Guimaras provinces. This industry is continuously marred with problems on fuel price increase, high cost of maintenance and increasing fees and requirements set by the Maritime Industry Authority. Cost and Returns Analysis was employed in determining the level of profitability. It showed a wide margin of profit between motorboats operating day and night and motorboats operating on day time only.
Thesis (undergraduate, Bachelor of Science in Economics)- University of the Philippines Visayas, Miag-ao, Iloilo
Keywords: Motorboat operation -- Iloilo City; Motorboat operation -- Jordan, Guimaras